Negative Pressure Wound Therapy saved a limb from amputation: A case report - Dwi Purnomo Setyo Budi; Mochamad Sadabaskara; Bontor Daniel Sinaga; Filberto Budhy (Journal of Orthopaedic Reports)
Large soft tissue defects resulting from high-energy trauma, such as traffic accidents, present significant challenges in wound management due to the high risk of infection, delayed healing, and functional impairment. Negative Pressure Wound Therapy (NPWT) has emerged as a valuable treatment modality for promoting wound healing in complex cases. By applying uniform subatmospheric pressure to the wound bed, NPWT aids granulation tissue formation, removes excess fluids, reduces bacterial colonization, and stabilizes the wound environment. This report presents a case of a 21-year-old male with a large soft tissue defect extending from the femur to the left foot, complicated by necrosis, gangrene and purulent exudate. The use of NPWT for approximately 2.5 months, facilitated rapid granulation and infection control, leading to successful skin grafting. The case highlights the efficacy of NPWT in managing large, infected wounds, improving outcomes, and reducing complications associated with extensive tissue loss. Early NPWT initiation, combined with surgical debridement and skin grafting, proves to be an effective approach in trauma-induced soft tissue defects.